The ecology and significance of below-ground bud banks in plants - Ott, Jacqueline P.; Klimešová, Jitka; Hartnett, David C. (Annals of botany, 2019)
Below-ground bud banks have experienced much recent interest due to discoveries that they (1) account for the majority of seasonal population renewal in many communities, (2) are crucial to regeneration following disturbance, and (3) have important consequences for plant population dynamics and plant and ecosystem function across a number of habitats. This review presents an overview of the role of bud banks in plant population renewal, examines bud bank life history, summarizes bud bank traits and their potential ecological implications, synthesizes the response of bud banks to disturbance, and highlights gaps to guide future research. The characteristics and life history of buds, including their natality, dormancy, protection and longevity, provide a useful framework for advancing our understanding of bud banks. The fate of buds depends on their age, size, type, location, and biotic and abiotic factors that collectively regulate bud bank dynamics. A bud bank can provide a demographic storage effect stabilizing population dynamics, and also confer resistance to disturbance and invasion. Regeneration capacity following disturbance is determined by interactions among the rates of bud natality, depletion and dormancy (meristem limitation), and the resources available to support the regeneration process. The resulting response of plants and their bud banks to disturbances such as fire, herbivory and anthropogenic sources determines the community's regenerative capacity. Vegetation responses to environmental change may be mediated through changes in bud bank dynamics and phenology. Environmental change that depletes the bud bank or prohibits its formation likely results in a loss of vegetation resilience and plant species diversity. Standardization of bud sampling, examination of bud banks in more ecosystems and their response to environmental variation and disturbance regimes, employment of stage-structured bud bank modelling and evaluation of the cost of bud bank construction and maintenance will benefit this expanding field of research.